2020
DOI: 10.1126/sciadv.aaz8700
|View full text |Cite
|
Sign up to set email alerts
|

Increased vaccine tolerability and protection via NF-κB modulation

Abstract: Improving adjuvant responses is a promising pathway to develop vaccines against some pathogens (e.g., HIV or dengue). One challenge in adjuvant development is modulating the inflammatory response, which can cause excess side effects, while maintaining immune activation and protection. No approved adjuvants yet have the capability to independently modulate inflammation and protection. Here, we demonstrate a method to limit inflammation while retaining and often increasing the protective responses. To accomplish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 82 publications
2
35
0
Order By: Relevance
“…Of the molecules we tested, honokiol and capsaicin proved to be effective at both limiting inflammation and potentiating the protective response. Through knockout studies, we demonstrate that the increase in antigen specific antibodies is independent from the anti-inflammatory activity, which is congruent with our previous studies (5). To determine if these small molecules could be improved by chemical synthesis, we explored derivatives of honokiol and found several promising candidates for potential use in vaccines.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Of the molecules we tested, honokiol and capsaicin proved to be effective at both limiting inflammation and potentiating the protective response. Through knockout studies, we demonstrate that the increase in antigen specific antibodies is independent from the anti-inflammatory activity, which is congruent with our previous studies (5). To determine if these small molecules could be improved by chemical synthesis, we explored derivatives of honokiol and found several promising candidates for potential use in vaccines.…”
Section: Introductionsupporting
confidence: 86%
“…We chose to analyze systemic levels of TNF-α and IL-6 because high levels of these cytokines are pyrogenic and have been correlated with undesirable vaccine-related side effects (15)(16)(17). We previously determined that CpG-induced TNF-α and IL-6 peak at 1 h postvaccination (5). Mice vaccinated with CpG demonstrated high levels of TNF-α (1067 pg/mL) ( Figure 1B).…”
Section: Exploration Of Small Molecule Nf-κb Inhibitors In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we observed the down-regulation of NF-κB signal in the post-BBIBP-CorV vaccination PBMC samples. Previous study suggested that the suppression of NF-κB signal likely alleviated the vaccine adverse reaction 29,30 , which might partially explain much less adverse reaction cases was reported by the vaccine recipients of BBIBP-CorV. Even though, the antibody productions of our participants were satisfactory.…”
Section: Discussionmentioning
confidence: 53%
“…In PBMCs from CHB patients, it has also been shown that anti–SIGLEC-3 mAb could reverse the effect and induce a cytokine response to the TLR-7 agonist, GS-9620 [ 128 ]. TLR agonists as vaccine adjuvants are currently under investigation for different human vaccines, including HBV vaccines, and appear promising in vaccine studies [ 129 , 130 ]. Vaccines containing particular TLR agonist(s) may activate specific TLR(s) and enhance vaccine efficacy without direct participation in protective immunity [ 131 , 132 ].…”
Section: Potential Of Tlr Agonists As Immunomodulatorsmentioning
confidence: 99%